The potential output gains from using optimal teacher incentives: An illustrative calibration of a hidden action model - Nirav Mehta (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
This note examines the potential output gains from the implementation of optimal teacher incentive pay schemes, by calibrating the Hölmstrom and Milgrom (1987) hidden action model using data from Muralidharan and Sundararaman (2011), a teacher incentive pay experiment implemented in Andhra Pradesh, India. Findings suggest that the introduction of optimal individual incentive-pay schemes could result in very large increases in output, about six times the size of the (significant) results obtained in the experiment.
Keywords: 330; hidden action; empirical contracts; teacher incentive pay